1977
DOI: 10.1021/ja00467a008
|View full text |Cite
|
Sign up to set email alerts
|

Heavy atom effects on the triplet lifetimes of naphthalene and phenanthrene

Abstract: 13) The partial charge for the H atom has been adjusted to give a rough match to the typical dipole strengths found for aliphatic CH stretching vibrations; cf. T. R. Faulkner, Ph.D. Thesis, University of Minnesota, 1976. (14) D. F. Burow, private communication. (15) The dipole strength, D (in cgs units of esu2cm2), is related to the infrared intensity A (In km/mol) by A = 2.5066 X 1036 D v, where v Is in cm-1. ( 16) This limit of about 2000 cm-1 arises through the need to employ fast detectors with a high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 10 publications
1
48
0
Order By: Relevance
“…25 However, our work and that of others has shown that in general singlet to triplet intersystem crossing (ISC) is the primary non-radiative singlet decay pathway operating in platinum containing π-conjugated structures. 18,[43][44][45][46] In addition, platinum acetylides with efficient ISC are expected to have very short fluorescence lifetimes (<100 ps). 18,47 Given these facts, and based on the observations reported herein, we believe that the reason for the reduced ϕ f and τ f in p-TBT and the longer oligomers is not due to enhanced non-radiative decay of the singlet state (i.e., singlet quenching).…”
Section: Excited State Properties Uv-visible Absorption Spectroscopymentioning
confidence: 99%
“…25 However, our work and that of others has shown that in general singlet to triplet intersystem crossing (ISC) is the primary non-radiative singlet decay pathway operating in platinum containing π-conjugated structures. 18,[43][44][45][46] In addition, platinum acetylides with efficient ISC are expected to have very short fluorescence lifetimes (<100 ps). 18,47 Given these facts, and based on the observations reported herein, we believe that the reason for the reduced ϕ f and τ f in p-TBT and the longer oligomers is not due to enhanced non-radiative decay of the singlet state (i.e., singlet quenching).…”
Section: Excited State Properties Uv-visible Absorption Spectroscopymentioning
confidence: 99%
“…Additionally, the oscillator strength of spin-forbidden T 1 ) S 0 absorptions can increase. 39 Musser et al 40 reported singlet ssion in polythienylenevinylene and its selenophene and tellurophene derivatives. They found no signicant differences in the (T 1 T 1 ) formation dynamics between the three polymers.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to compare these results with those of Miller et al 2 They examined the additivity of the internal heavy-atom effect by testing eq 1 where kbt is the observed 1,2,3,4…”
Section: Resultsmentioning
confidence: 92%